THE EFFECT OF PROVIDING TYPES OF BIOLOGICAL AND RHIZOBIUM FERTILIZERS ON SOYBEAN (Glycine max L) CROP PRODUCTION - Syamsafitri; Muhammad Rizwan; Nurhayati; Sri Hafnida Ritonga; Amalia (CV. Radja Publika, 2023)
This research aims to determine the effect of giving Biohayati fertilizer, giving Rhizobium bacteria and also the interaction of giving Biohayati fertilizer on soybean production. This research was carried out in Laut Tador Village, Batu Bara Regency, North Sumatra Province. At an altitude of ± 12 meters above sea level with flat topography. This research used a factorial RAK (randomized group design) with 2 treatment factors. The first factor is the provision of Bio-Biological Fertilizer, which consists of four levels, namely: B0 = No treatment, B1 = Bio-biotic solution with a dose of 18 ml/liter of water, B2 = Bio-biological solution with a dose of 20 ml/liter of water, B3 = Bio-biological solution with a dose of 22 ml/liter of water. The second factor is that the administration of Rhizobium bacteria is carried out at three levels, namely: R0 = no treatment, R1 = Rhizobium at a dose of 1.6 kg/plot (seeds mixed with Rhizobium solution), R2 = Rhizobium at a dose of 1.8 kg/plot (Rhizobium is watered in land). The results of the research show that the effect of providing Biohayati has a significant effect on soybean plant production, namely the number of pods and filled pods. The effect of giving Rhizobium bacteria has a significant effect on soybean plant production, namely the number of pods and filled pods. The interaction effect of giving Biohayati and Rhizobium bacteria on soybean production did not have a significant effect. Providing a biological solution at a dose of 22 ml/liter of water and Rhizobium at a dose of 1.6 kg/production plot to soybean plants is the best dose.